Successful Ageing with COPD: Physical and Psychosocial Adaption to Functional Decline. (3rd September 2018) - Southwell, Phillipa Jane; Crockett, Judith; Burton, Deborah; Gullifer, Judith
Abstract: There is considerable research regarding the adaption to functional decline associated with advanced (Stage IV) Chronic Obstructive Pulmonary Disease (COPD). This research has, however, primarily focused on physical and interventional strategies to manage disease progression and symptom burden, as opposed to the psychosocial strategies. To address this paucity, the current research explored the psychosocial strategies people with Stage IV COPD use to maintain quality of life towards the end of life. Eleven older people with Stage IV COPD living in regional Australia were interviewed to explore their experiences of ageing with COPD. The research used a theory-led analysis, informed by a Gadamerian hermeneutic phenomenological methodology, to examine participant data in relation to selection, optimisation and compensation theory (SOC). The participant stories reflected the use of selective strategies, from which a hierarchy of priority tasks emerged. Participants optimised their capacity to perform high priority tasks using a range of pragmatic and instinctive responses to ongoing change, which became more and more conscious and deliberate over time. Additionally, compensatory strategies more traditionally associated with COPD management were used to reduce the impact of symptoms. It is through the participant descriptions and perception of optimisation and compensation strategies and how they were implemented that the wider theme of 'mind over matter' emerged. The use of these strategies to adapt physically and psychosocially to COPD shows how the participants demonstrated resilience and used 'successful ageing' strategies to cope with ongoing functional decline.